2020
DOI: 10.22541/au.160075279.96631305
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Amounts of Thermal Vibrations and Static Disorder in Protein X-ray Crystallographic B-factors

Abstract: Crystallographic B-factors provide direct dynamical information on the internal mobility of proteins that is closely linked to function, and are also widely used as a benchmark in assessing elastic network models. A significant question in the field is: what is the exact amount of thermal vibrations in protein crystallographic B-factors? This work sets out to answer this question. First, we carry out a thorough, statistically sound analysis of crystallographic B-factors of over 10,000 structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…In our recent work 31 , we have shown that the amount of thermal vibrations is small in most proteins but is significantly large (50% or higher) for structures determined at both high resolution and high temperature (that is, room temperature). Unfortunately such structures are rare in the PDB, as most structures in the PDB are determined at cryogenic temperature to reduce the radiation damage 43 .…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…In our recent work 31 , we have shown that the amount of thermal vibrations is small in most proteins but is significantly large (50% or higher) for structures determined at both high resolution and high temperature (that is, room temperature). Unfortunately such structures are rare in the PDB, as most structures in the PDB are determined at cryogenic temperature to reduce the radiation damage 43 .…”
Section: Resultsmentioning
confidence: 95%
“…The magnitudes of thermal vibrations of a whole protein is defined as the mass-weighted averages of over all the nodes 31 , i.e., where i is the index of nodes, which include both protein atoms and added molecular surface nodes. m i are the mass of node i.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations